A note on the design of hp-adaptive finite element methods for elliptic partial differential equations - Houston, P; Süli, E (2005)
We introduce an hp-adaptive finite element algorithm based on a combination of reliable and efficient residual error indicators and a new hp-extension control technique which assesses the local regularity of the underlying analytical solution on the basis of its local Legendre series expansion. Numerical experiments confirm the robustness and reliability of the proposed algorithm. © 2004 by Elsevier B.V. All rights reserved.